PENGEMBANGAN MATERI AJAR TEKS CERITA PENDEK BERMUATAN KEARIFAN LOKAL MELAYU DALAM BENTUK FLIPBOOK UNTUK SISWA KELAS VIII SMP NEGERI 4 MEDAN - Arini, Rika; Atika Wasilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the development process, product design, and feasibility of a Malay local wisdom-based short story teaching material developed in the form of a flipbook for eighth-grade students at SMP Negeri 4 Medan. The teaching material was developed using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), which was limited to three stages: analysis, design, and development. The resulting product is an interactive digital flipbook designed to support the teaching and learning of short story texts. The findings indicate that the developed teaching material was categorized as highly feasible based on validation conducted by material experts, media experts, and an Indonesian language teacher. The material expert awarded a score of 88,64%, the media expert 93%, and the Indonesian language teacher 95%. Based on these findings, the Malay local wisdom-based short story teaching material in the form of a flipbook is considered suitable for use as supplementary instructional material to support the implementation of classroom learning. Keywords: Teaching Materials, Short Stories, Flipbook